Effects of cardamonin alleviate hyperalgesia and allodynia with possible involvement of monoaminergic pathways in chronic constriction injury-induced neuropathic pain mice model - Kaswan, Nur Khalisah (2021)
Neuropathic pain is chronic pain caused by the nerve's injury that accompanied with changes in the somatosensory system which is normally presented with hyperalgesia and allodynia. The mechanism of this condition is complex, hence, neuropathic pain patient frequently does not receive a significant benefit from current treatments. This situation might be due to an ineffective dose given, numerous adverse effects and drug delivered is not specific to the target. Nevertheless, our previous study on neuropathic pain discovered that cardamonin (a naturally occurring chalcone) have the potential to alleviate neuropathic pain symptoms in the chronic constriction injury (CCI) mice model. Hence, this present study aimed to further evaluate the possible monoaminergic pathway's involvement in cardamonin induced antihyperalgesic and antiallodynic effects in CCI mice model. The chronic constriction injury model was performed by placing one loose ligation on the ICR male mice's sciatic nerve to develop neuropathic pain condition. Day 14 post-surgery, four different cardamonin doses of 0.3, 3. 1 and 10 mg/kg were administered intraperitoneally to determine the effective dose of cardamonin to alleviate hyperalgesia and allodynia. The behavioral responses were assessed using the Hargreaves plantar test (thermal hyperalgesia) and the von-Frey filament test (mechanical allodynia). Cardamonin at 10mg/kg was shown to exhibit a significant anti- hyperalgesia and anti-allodynia properties in the CCI mouse model. The investigation of serotonergic involvement was performed by depleting the serotonergic level using ρ- chlorophenylalanine (PCPA, 100 mg/kg, i.p), a serotonin synthesis inhibitor, for four consecutive days before cardamonin treatment. Our results indicate the antihyperalgesic and antiallodynic effects of cardamonin were reversed after administration of PCPA. Following this, the mice's pretreatment with several 5-HT receptor subtypes antagonists before cardamonin 10 mg/kg treatment implies that serotonin receptors 1, 1A, 1B, 2A, 3, 6 and 7 were involved in the antihyperalgesic and antiallodynic effect of cardamonin. Further evaluation of protein expression using western blot following cardamonin treatment appear to upregulate the 5-HT1A protein expressions in mice’s spinal cord, brainstem and cerebral cortex. Our finding suggests that cardamonin modulates the 5- HT1A receptor to induce the descending serotonergic inhibitory system, probably via the PAG-RVM-spinal cord pathway activation. Following this, the noradrenergic system's involvement was evaluated by administering non-specific α- and β-adrenergic receptor antagonists before cardamonin treatment. Further investigation into the effect of cardamonin on specific adrenergic receptors subtypes revealed that α1, α2, β1 and β2 was important in cardamonin induced antineuropathic effect in the CCI mice model. Our findings demonstrate that cardamonin can up-regulate α2A receptor expression. This finding suggests the inhibitory effect of cardamonin is likely to be modulated via the upregulation of this receptor activity in the brainstem and spinal cord. Therefore, we postulated that the pain inhibitory effect of cardamonin in CCI-induce mice is probably mediated by the action of serotonin and noradrenergic receptors within the central and peripheral nervous system. Precisely, the inhibitory action of cardamomin might be modulated via 5-HT1A and α2A receptors in the brainstem and spinal cord. In conclusion, our findings demonstrated that monoaminergic pathways were involved in mediating the antineuropathic effect of cardamonin in CCI induced neuropathic pain model and can be a new therapeutic approach for neuropathic pain management.